Immune system effectors as biomarkers of prognosis after acute burns in a case-control study - Alejandro Ferrari; Lorena Di Croce; Sabrina Saavedra; Marisel Hartwig; Omar Perrone; María Alejandra Guzmán (Academia Biology)
Burns are a global health problem due to frequent complications, which lead to systemic inflammation, acute respiratory distress syndrome, multiorgan dysfunction, and death. Following the initial injury, it has been demonstrated that the immune system plays a key role in early inflammation, tissue regeneration, and the response against pathogens. In this study, the performance of laboratory determinations as biomarkers of prognosis in acute burned patients was evaluated in a retrospective case-control protocol. Laboratory determinations were immunoglobulin G (IgG), immunoglobulin M (IgM), C-reactive protein (CRP), complement C4 protein (C4), total serum protein (TP), albumin, prealbumin, cholesterol (CHOL), pseudocholinesterase activity (CHE), and transferrin. Patients in the deceased group (DG) showed lower initial IgG levels (p < 0.05) than patients in the survivor group (SG), with a negative predictive value (NPV) of 0.86, and this difference persisted during the hospitalization period. Furthermore, DG patients showed a decrease in CHOL and CHE during the hospitalization period (NPV of 0.86), a tendency that was not observed for the SG. Albumin, TP, C4, and transferrin showed lower initial values in DG than the SG, with a strong correlation with the total burned surface area (TBSA). These results indicate that IgG, CHOL, and CHE measurement might provide useful information for medical intervention independently of the TBSA and suggest that the measurement of TBSA-linked parameters might help to estimate the severity of burns more objectively. In this paper, the causes and implications of the alteration of effector molecules of the immune system are discussed.